Widow inheritance and HIV/AIDS in rural Uganda - Mabumba, E D; Mugyenyi, P; Batwala, V; Mirembe, J; Liljestrand, J (Tropical doctor, 2007)
Despite current efforts to combat HIV/AIDS through behavioural change, ingrained socio-cultural practices such as widow inheritance in south-western Uganda has not changed. Low education, unemployment, dowry, widows’ socioeconomic demands and the inheritor’s greed for the deceased’s wealth, influence widow inheritance. Voluntary counselling and testing is needed for the widows and their inheritors; formal dowry should be removed from marriage and widow inheritance stripped of its sexual component.